De la masculinité de François Bayrou. Une analyse en creux des conditions d’efficacité d’un registre identitaire controversé - Clément Arambourou (Genre, Sexualité et Société)
This study of François Bayrou focuses on the political use of masculine identity in the French presidential election campaign of 2012. On the one hand, the MoDem’s President can use masculinity to criticize Nicolas Sarkozy and to distinguish himself from the French president. On the other hand, the metapragmatic register which characterizes masculinity in the political field hinders François Bayrou’s gender performance. His difficulties underline the necessity for masculinity to conform to two main standards of political legitimacy: rootedness and change.